TANGIBLE CONDITIONS OF HUMAN RESOURCES FACTORS IN MSME DECADE OF COVID-19 IN CITY OF BANDUNG-WEST JAVA-INDONESIA - Deden Sutisna; Uce Karna Suganda (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the condition of the tangible factors of the human resources of MSME business actors in Bandung City at the time of COVID-19. The consideration of this research was taken because this sector has a large population, is used by various professional and educational backgrounds, and this effort is flexible and becomes a helper for the economy of the poor, especially when COVID-19 became a world pandemic. The research method used is verification, descriptive and comparative with a total sample of 45 MSME actors. Data obtained by distributing google form questionnaires, after tabulation, the data is tested by validity, reliability, classical assumptions and normality. To answer the research objectives, the data was processed using SPSS Version 25 with the help of correlation coefficients, determination and descriptive analysis. The results showed that the competency of the human resources of MSME actors was very good, however, when viewed partially, the knowledge and skills they had were only good enough. This means that there are other competency elements that have a strong contribution to this variable, namely the attitude of them. Meanwhile, the current work environment is quite conducive and the performance is in very good condition. Based on the research results, it can be concluded that the tangible factor of human resources of MSME actors in Bandung City has different conditions, and has a strong relationship with intangible factors.